Studi Fenomenologi: Pengalaman Perawat Dalam Penggunaan APD Untuk Pencegahan Infection Control di Ruang IGD RS Rizani Paiton Probolinggo - Husnul khotimah; S. Tauriana; Fatilah (Aafiyah: Jurnal Multidisiplin Ilmu, 2024)
Introduction: Personal Protective Equipment (PPE) is a set of safety equipment used by workers to protect all or part of their body from possible exposure to potential hazards in the work environment for accidents and work-related diseases. A nurse in providing health services to patients must have good knowledge and attitudes regarding the use of PPE in every provision of health services to patients. Compliance with the health and safety behavior of nurses in hospitals is very important, because even the smallest actions of nurses can pose a risk to nurses and patients. Research Method: This research uses a qualitative method with a phonomenological approach, which aims to describe, interpret and analyze data in depth regarding the Phenomenological Study: Nurses' Experiences in Using PPE to Prevent Infection Control in the Emergency Room at Rizani Paiton Hospital, Probolinggo. Six participants were selected based on research criteria and were saturated. Data was collected by in-depth interviews and observation. Interpretative Phenomenological Analysis (IPA) analysis was used in data analysis. Three themes were identified in this research: (1) experience of using PPE among nurses (2) Prevention and treatment of infections in hospitals (3) Nurse compliance. The research results are supported by the fact that clients use PPE well. It was concluded that there was experience of nurses in using PPE to prevent infection control. The conclusion is that there is a relationship between nurses' compliance in using PPE in the hospital environment.